Tidal Energy and Main Resources In the Persian Gulf - Gorji-Bandpy, Mofid; Azimi, Mohammadreza; Jouya, Mohsen (Distributed Generation & Alternative Energy Journal, 2013)
Due to increasing concern over global climate change, many policy makers worldwide have accepted the importance of reducing greenhouse gas emissions, in particular from the electricity industry. Tidal generation has a significant advantage over many other forms of renewable generation as it is almost perfectly forecastable over long time horizons. Thus, incorporating tidal generation into an electricity system should be less challenging than other forms of renewable generation which are relatively unpredictable. In this article, we discussed about the capacity benefit of tidal generation, especially in Iran.